Application of the Project Based Learning Model to Learning Educational Statistics - Risa Wara Elzati (STAIN Bengkalis, 2024)
The aim of this research is to determine the effect of the project based learning model on educational statistics. This type of research is experimental research with a total sampling model. The sample in this study consisted of 30 students with One Group Pretest-Posttest. Data analysis used the average value of pretest (before learning) and posttest (after learning) learning outcomes in the research class and compared the average learning outcomes before and after learning with the project based learning model. Data was obtained from respondents by giving written test questions (essays). The research results show that there is a significant influence on the average student learning outcomes after learning with the project based learning model in learning educational statistics courses. Students have a positive perspective on the application of the project based learning model in learning, apart from that students believe that the projects/assignments they work on help them understand lecture material, increase motivation in learning outcomes and trigger ideas and creative thinking in solving problems so that they get good results in the projects they work on.